Septal transplants restore maze learning in rats with fornix-fimbria lesions. - Dunnett, S; Low, W; Iversen, S; Stenevi, U; Björklund, A (1982)
In a study of the capacity of neural grafts to promote functional recovery in rats with fimbria-fornix lesions, 5 groups of rats were studied behaviourally and with acetylcholinesterase (AChE) histochemistry: (1) sham-operated controls; (2) bilateral fimbria-fornix lesions; (3) bilateral lesions plus bilateral solid embryonic septal grafts to the lesion cavity; (4) bilateral lesions plus bilateral embryonic septal suspension injections into the hippocampus; and (5) bilateral lesions plus bilateral solid embryonic locus coeruleus grafts to the lesion cavity. Seven months were allowed for growth of the grafts and reinnervation of the host hippocampus prior to behavioural testing. The control rats were able to rapidly learn a rewarded alternation task, while the performance of animals with bilateral fimbria-fornix lesions alone remained at a chance level. Both types of septal grafts (rich in cholinergic neurones) but not the locus coeruleus grafts (rich in noradrenergic neurones) reversed the impairment. Behavioural recovery correlated significantly with AChE-positive fibre ingrowth from the grafts into the denervated host hippocampus. However, the septal grafts did not ameliorate the lesion-induced disturbances in spontaneous activity or spontaneous alternation. Thus, the observed behavioural recovery appears specific to the conditioned alternation task and dependent upon cholinergic reinnervation of the hippocampus.